Synthesis and Structure of Oxygen Deficient Lead-Technetium Pyrochlore, the First Example of a Valence V Technetium Oxide - Kennedy, Brendan J.; Ablott, Timothy A.; Avdeev, Maxim; Carter, Melody L.; Losurdo, Linda; Saura-Muzquiz, Matilde; Thorogood, Kevin J.; Ting, Jimmy; Wallwork, Kia S.; Zhang, Zhaoming; Zhu, Hanliang; Thorogood, Gordon J. (Frontiers in Chemistry, 2021)
The structure of lead-technetium pyrochlore has been refined in space group with a = 10.36584(2) Å using a combination of synchrotron X-ray and neutron powder diffraction data and confirmed via Electron Diffraction. The oxide is found to be oxygen deficient with a stoichiometry of Pb2Tc2O7-d. Displacive disorder of the Pb cations is evident from the refinements, as has been observed in Bi2Tc2O7-d. X-ray absorption spectroscopic measurements at the Tc K-edge demonstrate the valence of the Tc is greater than 4.0 as anticipated from the refined oxygen stoichiometry. Raman spectroscopy confirms the presence of disorder leading us to conclude that this pyrochlore is the first example of a valence V technetium oxide.